Відносини між громадськими виконавчими комітетами та Радами робітничих, солдатських і селянських депутатів на прикладі Харківської, Чернігівської та Полтавської губерній - Самсонова, І.В. (Сумський історико-архівний журнал, 2010)
The evolution of relationship between public executive committees and Soviets of workers’, solders’ and peasants’ deputies by the example of Kharkiv, Chernihiv and Poltava provinces during the period of March-October 1917 is examined in the article.